ANALISIS EFEKTIVITAS PELAKSANAAN PENAGIHAN PAJAK AKTIF DENGAN MENGGUNAKAN KONSEP VALUE FOR MONEY - Anjarsari, Ni Nyoman Vitria; Noviari, Naniek (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The purpose of this study are to determine effectiveness of implementation tax collection actively using letters of reprimand, forced letter, and a warrant for the seizure of using the concept of value for money in Tax Office Primary in Province of Bali in 2010-2015. Analysis technique used is effectiveness ratio. Data collection methods used were interviews and documentation Tax Office Primary in the Province of Bali. Letter of reprimand and forced letter Tax Office Primary in the Province of Bali in 2010-2015 was classified as less effective, while the warrant for the seizure of the Tax Office Primary in the Province of Bali in 2010-2015 relatively ineffective. Results are based on the level effectiveness of the active implementation tax collection by using a letter of reprimand and forced letter is between 60-80 percent, while level effectiveness of the implementation tax collection actively using the seizure warrant was under 60 percent.
Keywords: effectiveness, letter of reprimand, forced letter, the seizure warrant, value for money